Actor-Network and Community’s Adaptation under Special Ecconomic Zone Develpment ; Case Study of Notheastern Thailand - Thammawat, Phanyupha; Chamaratana, Thanapauge (CENTRAL ASIA AND THE CAUCASUS, 2022)
This article examined the patterns and interplay of an actor-network in Thailand’s border special economic zone development and identified the factors affecting its capability in communities’ livelihood restoration. An exploratory mixed method was applied. The documentary research, an in-depth interview with 35 key informants, and non-participant observation were conducted to trace power relations within a network. The survey of 375residents, and multiple regression techniques were adopted to identify the influential factors in communities’ adaptation. Results revealed that the network of SEZ establishment was overlayed with a preexisting network of locals’ livelihoods, through a land right reform. The post-coup legislation was a key actor that dominated the relational flow within a network. Whereas the statistical analysis shows that local communities are not against the idea of SEZ, but more decentralization and constructive engagement of provincial authorities and community’s participatory platform are required as supporting factors for communities under the transition.